Scholarship of Teaching and Learning in Speech-Language Pathology and Audiology : Evidence-Based Education. - Ginsberg, Sarah (Plural Publishing, Inc., 2011)
By sharing what evidence-based education (EBE) methods are available, this book aims to increase the efficacy of clinical education in a variety of fields and at the same time, provide valuable insights to communication science and disorders faculty members as to how they can contribute to the growing body of evidence regarding teaching, often referred to as the scholarship of teaching and learning (SOTL).